THE EFFECT OF WORKLOAD AND ORGANIZATIONAL SUPPORT ON EMPLOYEE PERFORMANCE IN THE GENERAL BUREAU OF BP BATAM - Roni Agustiadi; Mira Yona; Hanafi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Employee performance in public sector organizations is influenced by organizational factors such as workload and organizational support. This study aims to analyze the effect of both variables on the performance of employees in the General Bureau of BP Batam, both partially and simultaneously. A quantitative approach with a cross-sectional design was employed, involving 20 employees from three work units. Workload was measured using the NASA Task Load Index (NASA-TLX), organizational support was assessed using the Survey of Perceived Organizational Support (SPOS), and employee performance was evaluated based on the dimensions of task performance and contextual performance, all using a five-point Likert scale. Data were analyzed using multiple linear regression (SPSS 24.0). Results indicated that workload (p = 0.875) and organizational support (p = 0.158) did not have a significant effect on employee performance, although the directions of the relationships were consistent with theoretical predictions — negative for workload and positive for organizational support. The non-significant findings are attributed to employees' adaptive capacity, perceptual homogeneity among respondents, and limitations in sample size. This study contributes to understanding the dynamics of employee performance at BP Batam and recommends future research with larger samples and the inclusion of mediating variables.